1991
DOI: 10.1177/0310057x9101900220
|View full text |Cite
|
Sign up to set email alerts
|

Experience with the Laryngeal Mask Airway in Two Hundred Patients

Abstract: Observations were recorded from two hundred consecutive insertions of the laryngeal mask airway (LMA). They were undertaken by 27 anaesthetists most of whom had no previous experience of its use. A clinically patent airway was obtained in 94% of patients and in the majority of these (76%) the LMA was positioned correctly at the first attempt. There were twelve cases of failed insertion. Nine of these were as a result of an inability to pass the LMA correctly into the hypopharynx while in the remaining three ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 22 publications
4
20
0
1
Order By: Relevance
“…Some authors have reported failure rates comparable with our own, both in adults and in children [5,17–19]. One group, examining the success rates of anaesthetists with little or no previous experience of the LMA, had a 24% first‐insertion failure rate [20].…”
Section: Discussionsupporting
confidence: 73%
“…Some authors have reported failure rates comparable with our own, both in adults and in children [5,17–19]. One group, examining the success rates of anaesthetists with little or no previous experience of the LMA, had a 24% first‐insertion failure rate [20].…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, we focused particularly on the performance and efficacy of SLIPA by novice personnel in the present study. McCrirrick et al [9] defined the 'novice' airway provider as someone who has previously used LMA less than 15 times. However, in the present study, 'novice' personnel are who has previously used any kind of LMA or SLIPA less than 5 times, because there was a short learning curve of about 13 cases for insertion of SLIPA in a previous study [10].…”
Section: Discussionmentioning
confidence: 99%
“…Because the larynx is not directly stimulated by laryngoscope or tube, respiratory and cardiovascular responses to insertion of an LMA are decreased in comparison to an ETT5–7; in addition, there is a decreased risk of damage to the teeth from the laryngoscope. The incidence of coughing, gagging, and patient movement at the time of airway device removal is also reduced 8–10. There is also evidence that postoperative respiratory mechanics are improved for those patients who have an LMA versus ETT who are moderately obese (body mass index 30 kg/m 2 ) 11.…”
Section: Discussionmentioning
confidence: 99%